Klebsiella pneumoniae in New Zealand sea lions : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Veterinary Science at Massey University, Manawatū, New Zealand - Pinpimai, Komkiew (Massey University, 2018)
Klebsiella pneumoniae has been circulating in New Zealand sea lions since the outbreaks during the breeding seasons of 2001/02 and 2002/03 in Sandy Bay, on Enderby Island, Auckland Islands. A large number of pups have since died from K. pneumoniae every year during the breeding season. In order to prevent and control this infection, baseline data including bacterial phenotype and genotype, geographic distribution of the pathogen, and the immune response to the pathogen, have to be established. In this study, hypervirulent (HV) K. pneumoniae was isolated from different sources including New Zealand sea lion (NZSL) pups from different breeding sites, and characterised using a combination of biochemical, phenotypic tests, serological analysis and genotyping via whole genome sequencing. Isolates from pups, substrate samples from different breeding sites, a NZSL adult and birds, all had a close genetic relationship. The isolates have the same basic characteristics including a hypermucoviscous phenotype, serotype 2, and sequence type 86. This suggested clonality of this pathogen. The geographic distribution of the pathogen was found to be Enderby Island, Dundas Island, Campbell Island, and the Otago Peninsula (New Zealand mainland). The isolates analysed were all susceptible to commonly used antibiotics, with the exception of ampicillin. The HV isolates from pups were able to utilise a wide panel of carbon and nitrogen sources and had activity in a wide range of pH from 4.5 to 10, supporting the ability of this pathogen to survive in diverse environments. The findings in this thesis also suggest that the environment can be a reservoir for a short time period. For the long term, between breeding seasons, New Zealand sea lion adults and birds that live around the breeding site are potential reservoirs. The HV isolates from pups were resistant to some innate immune responses, including serum killing ability, oxidative killing ability and phagocytosis by neutrophils and monocytes. Overall, this study provided phenotypic and genotypic information on K. pneumoniae isolated from NZSL pups, as well as some information about innate immune responses to this pathogen, which can aid in the prevention and control of this infection.
Keywords: Hooker's sea lion; Pathogens; New Zealand; Infections; Prevention; New Zealand; Klebsiella pneumoniae